2019
DOI: 10.5505/biodicon.2019.66376
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the effect of different drying temperatures on the content and chemical composition of essential oil of sage (Salvia officinalis)

Abstract: The aim of this experiment was to determinate the effect of different drying temperatures on the content and chemical composition of essential oil of sage (Salvia officinalis L.). Essential oil isolated for 3 hours from fresh and oven dried leaf samples (at 35°C, 45°C, 55°C and 65°C) by using Clevenger type apparatus was analyzed with GC-MS. The content of volatile oils (%) in different drying temperatures was in the order of: fresh leaf sample (0,483%), dried leaf sample at 35 °C (1,837%), at 45 °C (1,550%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The amounts of the major constituents of current findings such as α-thujone (13-35.8%), camphor (7-20.2%) and 1,8-cineole (6.9-14.15%) were largely within the range of the proposed standards. Most of the compounds found in the present study have been reported in other studies on S. officinalis with different amounts (Mirjalili et al 2006, Ben-Farhat et al 2016, Rguez et al 2018, Katar et al 2019).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The amounts of the major constituents of current findings such as α-thujone (13-35.8%), camphor (7-20.2%) and 1,8-cineole (6.9-14.15%) were largely within the range of the proposed standards. Most of the compounds found in the present study have been reported in other studies on S. officinalis with different amounts (Mirjalili et al 2006, Ben-Farhat et al 2016, Rguez et al 2018, Katar et al 2019).…”
Section: Resultssupporting
confidence: 82%
“…Therefore, methods that can produce a healthy medicinal plant with more effective substances may be needed (Azarnivand et al 2010). Since climatic conditions cannot be controlled and managed, planting time, agronomic practices and especially harvesting time are the most critical factors in the optimal production of volatile oil and its quality (Lakušić et al 2013, Katar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with these findings, it were mentioned that the essential oil content increased until full flowering stage and then began to decline [Németh 2005]. In addition, in the studies conducted by Jankovsky and Landa [2002], Rey et al [2004] and Katar et al [2021], the essential oil contents were found to be 0.10-1.80%, 0.80-1.30% and 0.17-0.96%, respectively.…”
Section: Resultsmentioning
confidence: 77%
“…On the other hand, the lowest fresh and dry leaf + flower yields were recorded from before-flowering period (5.94 and 1.63 t ha -1 , respectively) -Tables 1 and 2. Katar et al [2021] reported that they obtained 12.22 t ha -1 fresh leaf + flower yield from a 3-year-old hyssop plant harvested during full flowering. The difference of these results may be due to the difference of the plant material used in the studies (different genotypes and ages) and the changing ecological conditions of study areas such as temperature, light intensity etc.…”
Section: Resultsmentioning
confidence: 99%